Keseimbangan Hak dan Kewajiban Para Pihak Pada Tahap Pra-Kontraktual Informed Consent di Rumah Sakit Zainab Pekanbaru - Ruziqna, Ananda; Firdaus, Firdaus; Dasrol, Dasrol (Jurnal Ilmiah Wahana Pendidikan, 2024)
The balance of the parties at the pre-contractual stage of informed consent at Zainab Pekanbaru Hospital is interesting to study in depth. This is because there are still many incidents where the patient and the hospital have not maximized the implementation of the pre-contractual stage even though informed consent has been carried out. The purpose of this study is, First, to find out how the balance of the parties is applied in the pre-contractual Informed Consent stage at Zainab Hospital Pekanbaru. Second, find out what conditions lead to non-fulfillment of the balance between the parties in the Informed Consent pre-contractual stage at Zainab Pekanbaru Hospital. This research uses the type of empirical legal research or sociological legal research. The sample in this study was Doctor, Nurse, and Patient of the Zainab Mother and Child Hospital, Pekanbaru City. The analytical tool in this study is a qualitative method. This study found that there were things that were less than optimal in reality on the ground, so it was necessary to anticipate them with maximum effort. This study concludes that, First, the application of the principle of balance of the parties in the pre-contractual informed consent stage at Zainab Pekanbaru Hospital in fact, not reached balance. The hospital has tried its best to implement the principle of balance as best as possible, but there are some patients who have problems implementing the principle of balance. Second, the situation that caused the principle of balance between the parties to not be fulfilled in the pre-contractual stage of informed consent at Zainab Hospital in Pekanbaru was caused by both parties. First, the circumstances that cause the patient's principle of balance to not be fulfilled consist of three causes, the first is the patient's lack of knowledge of his rights and obligations. This is divided into 3 causes, namely the patient's level of education and experience, lack of information and social culture and economics. Second, the patient does not provide honest and complete information about the disease he is suffering from. Third, the patient does not understand the doctor's explanation, this is caused by 3 things, namely, the influence of age, the influence of education, the influence of work and at the pre-contractual stage, informed consent was not explained. Second, the situation that causes the doctor's principle of balance to not be fulfilled, in the patient-doctor relationship, communication is active-passive. Doctors are active and patients are passive and only answer when asked or act after being ordered by the doctor. The communication conveyed is also not clear, because patients lack medical terminology, and doctors do not provide opportunities for patients to ask further questions about their medical condition.